Muhammad Bin Abdul Wahab : Akar Seruan Islam murni Gerakan Salafi Di Indonesia (EL-FIKR: Jurnal Aqidah dan Filsafat Islam, 2023)
Salafi is an Islamic reform movement that claims to be a group that follows pure Islamic teachings such as salafu al-shalih. This group is referred to as Wahhabis by other groups, because this group is attributed to its founder, Muhammad bin Abdul Wahab. Of course, between followers and founders more or less have a correlation between the two in various aspects. The purpose of this study will examine how the correlation is using qualitative research, especially using library instruments and observation. Starting from his teachings, to his method of preaching. Furthermore, the data collected will be analyzed using a phenomenological and philosophical approach. Looking at previous studies that discussed only the correlation of teachings, and had not touched the realm of da'wah methods explicitly. Thus, efforts to correlate to the level of the method of preaching came to the fore. The results of this study conclude that the da'wah launched by the salafi movement is correlated with the doctrine of its founder, namely calling for pure Islam that returns to the Al-Qur'an and al-Sunnah. Not only that, the method of preaching was the same, namely through something that was very influential in their respective eras. If Muhammad bin Abdul Wahhab went through the leaders, then the salafi movement in Indonesia today is through social media which can be seen by many people.